2007
DOI: 10.1016/j.bmc.2006.09.058
|View full text |Cite
|
Sign up to set email alerts
|

1-Methylpyridinium-4-(4-phenylmethanethiosulfonate) iodide, MTS-MPP+, a novel scanning cysteine accessibility method (SCAM) reagent for monoamine transporter studies

Abstract: A novel substituted cysteine accessibility method (SCAM) reagent was developed for monoamine uptake transporters. The new reagent, MTS-MPP + , was a derivative of the neurotoxin and transporter substrate MPP + . MTS-MPP + labeled cysteine residues introduced into the serotonin transporter protein. Although it did not prove to be a substrate, as is MPP + , it appears to label cysteine residues lining the permeation pore of the transporter more readily than currently-available nonspecific SCAM reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The results were confirmed by additional SCAM studies using MTS‐MPP + , a novel monoamine transporter SCAM reagent shown to be more potent at SERT than MTSET (Gallardo‐Godoy et al 2007). These results support a model where F556C/hSERT is exposed to the hydrophilic environment of the permeation pathway and may suggest that F556C/hSERT is localized close to the substrate binding site or in a conformationally sensitive site that makes F556C/hSERT accessible to MTS reagents near the entrance to the substrate permeation pathway.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The results were confirmed by additional SCAM studies using MTS‐MPP + , a novel monoamine transporter SCAM reagent shown to be more potent at SERT than MTSET (Gallardo‐Godoy et al 2007). These results support a model where F556C/hSERT is exposed to the hydrophilic environment of the permeation pathway and may suggest that F556C/hSERT is localized close to the substrate binding site or in a conformationally sensitive site that makes F556C/hSERT accessible to MTS reagents near the entrance to the substrate permeation pathway.…”
Section: Discussionmentioning
confidence: 72%
“…To confirm and validate our experiments, additional SCAM studies were performed using MTS-MPP + , a novel monoamine transporter methanethiosulfonate reagent proven to be more potent at SERT than MTSET (Gallardo-Godoy et al 2007). Consistent with the results above, F556C/hSERT was the only mutant that showed a Cells were plated and transfected as described in Materials and Methods.…”
Section: Substitution Of Phenylalanine At Position 556 With Serine Rementioning
confidence: 64%
See 1 more Smart Citation
“…Ligand synthesis: 4-( pyridin-4′-yl)benzenethiol was synthesized according to the literature 49,50 with minor modifications. A detailed protocol is available in the ESI.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…Thiosulfonates are structural motifs in the antibacterial agent allicin [50] . Thiosulfonates exhibit also biological properties such as antifungal, antimicrobial [51,52] and anticancer activities, [53] and also used as cysteine scanning reagents [54,55] . Recently, thiosulfonates have been used as synthetic precursors to incorporate sulfones and thioethers into organic molecules [56] …”
Section: Electrochemical Synthesis Of Thiosulfonatesmentioning
confidence: 99%